Successful Wildlife Conservation Requires Good Governance - Pomeranz, Emily F.; Hare, Darragh; Decker, Daniel J.; Forstchen, Ann B.; Jacobson, Cynthia A.; Smith, Christian A.; Schiavone, Michael V. (Frontiers in Conservation Science, 2021)
Public wildlife management in the United States is transforming as agencies seek relevancy to broader constituencies. This presents an opportunity for conservation program design and evaluation to be elevated in importance. We argue that success in wildlife conservation in the U.S. requires assessment of both decision-making processes and management results in relation to four questions: conservation of what, under what authority, for what purposes, and for whom?